Investigation of coping strategies of the students with disabilities - A. A. Kiseleva; M. Yu. Kuzmin (Acta Biomedica Scientifica, 2017)
The investigation is directed at studying peculiarities of the coping behavior of students with disabilities. The author using the sample of 200 students with and without disabilities studies differences in expressiveness of various strategies of coping behavior with the help of Leontyev Viability Test, Ways of Copying Behavior by S. Folkman & R. Lazarus and E. Heim's coping test. The author concludes that in general the students with health peculiarities rarely take responsibility for the events in their life (z = -2.92; p < 0.01), rarely analyze the situations and their possibilities (z = -1.99; p < 0.05) and more often try to distance from the problems (z = 2.34; p < 0.02). According to our data obtained such students have problems with coping-strategies in the cognitive sphere (z = 2.15; p < 0.05). In addition, the subjects with health issues demonstrate problems with coping strategies in the cognitive sphere. We also revealed the coping strategies peculiarities of those disabled since childhood and of those who became handicapped later. The peculiarities of coping behavior of the latter ones are, first of all, the prevailing of the nonadaptive coping strategies mostly escaping (z = -3.4; p < 0.01) and low level of hardiness (z = -5.61; p < 0.01). The data obtained are planned to be used in the sphere of rehabilitation of the handicapped subjects in the higher and secondary professional schools.